Effect of Hot Pack Administration on Shivering in Post Sectio Caesarea Patients with Spinal Anesthesia - Prameswari, Diah; Setya, Intan Eka; Shahab, Davis Achmadi; Ratnasari, Dezylia Ayu; Mulyati, Wiwin; Novita, Ita (Health Gate, 2023)
The impact that often arises after spinal anesthesia in post-cesarean section patients is shivering which is characterized by fasciculations of the skeletal muscles in the face, head, jaw, trunk or extremities that last more than 15 seconds. The incidence of post-anesthesia shivering in patients undergoing spinal anesthesia reaches 33-56.7%. Giving hot packs has been proven to be effective in treating hypothermia in post-cesarean section patients. Heat therapy using hot packs will restore body temperature quickly. This study aims to identify the effect of giving hot packs with shivering. The research design was pretest posttest control group design with 32 respondents, consisting of 16 treatment groups and 16 control groups taken by accidental sampling. This research was conducted in January 2020 in the High Care Unit Room, Aminah Islamic Hospital, Blitar. The results of this study showed that the administration of shivering scale hot packs in the treatment group decreased significantly to 0 while the control group experienced a less significant decrease in the shivering scale, namely to 1. Statistical test This study used Mann Whitney with a p-value of 0.000. This means that giving hot packs has an effect on shivering in post sectio caesarea patients with spinal anesthesia. Hot packs can be used asalternative therapy to reduce shivering in post sectio caesarea patients with spinal anesthesia